1973
DOI: 10.1002/art.1780160111
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a cobra venom factor on complement and adjuvant‐induced disease in rats

Abstract: The parenteral administration of mycobacterial adjuvant into rats induces an arthropathy which is generally believed to be due to cellular hypersensitivity. The role of complement in this phenomenon has not been defined. The levels of individual complement components were measured in sera of normal and adjuvant-treated rats. The effect of decomplementation with cobra venom factor (CVF) was studied in adjuvant-induced disease (AID). It was found that C9 is elevated in AID; and that CVF temporarily depletes C3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Depletion of C3 by CoF delayed the onset of arthritis in these animals until the C3 levels were returning toward normal values (32). At moderate doses, with 20% complement suppression, CoF was ineffective in inhibiting bovine serum albumin antigen-induced arthritis in New Zealand white rabbits (33).…”
Section: Discussionmentioning
confidence: 93%
“…Depletion of C3 by CoF delayed the onset of arthritis in these animals until the C3 levels were returning toward normal values (32). At moderate doses, with 20% complement suppression, CoF was ineffective in inhibiting bovine serum albumin antigen-induced arthritis in New Zealand white rabbits (33).…”
Section: Discussionmentioning
confidence: 93%
“…Complement depletion by cobra venom in Freund's adjuvant arthritis in rats delays the onset of arthritis in these animals (Kourounakis, Nelson, and Kupusta, 1973). Whether the relatively low numbers of animals having arthritis in our work compared with the Warren model is due to the complement deficiency, we are unable to state at present.…”
Section: Discussionmentioning
confidence: 64%
“…Humoral involvement of anti-mycobacterial antibody has been described [6], and the delayed development of adjuvant arthritis after treatment with cobra venom factor [32] also suggests a role for humoral immunity in this model. However, WALZ et al [33] reported that decomplementation with cobra venom factor had no effect on the onset of inflammation in adjuvant arthritis.…”
Section: Discussionmentioning
confidence: 98%